Factors affecting household insurance in Singapore. - Lee, Chang Wei. (2008)
Many Singaporeans now own properties of their own. Many don’t have household insurance to protect their property. Most mistakenly believe that Housing Development Board (HDB) will cover all losses. We identify the cause of this situation & make helpful recommendations in increasing household insurance purchases.